EXPERIMENTAL STUDY ON HIGH PERFORMANCE CONCRETE USING DIFFERENT TYPES OF AGGREGATE - Magesh, Mr. A.; Kumar, Mr.S.Udaya (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
A new generation of concrete, Highperformance of concrete has been developed of itsoutstanding strength durability performanceshows a very promising future in constructionapplication in this paper several possibilities areexamined for reducing the price of producinghigh performance concrete and to minimize theability of normal concrete. The following types ofcoarse aggregate were used to produce theconcrete; secondary aggregate; marble; lightweight aggregate (pumice) and natural mineral(gravel). The concrete contain a highly effectiveSuper plasticizer and metakoline. Mechanicalproperties and water absorption sharplyincreased during early stage approachingasymptotic valves, depending on design strengthcodes. Results of 28 days of curing light weightaggregate gives the high mechanical properties.When estimated with the conventional concrete.These experimental results demonstrate that thelight weight aggregate strongly influences themechanical and durability properties withoutbasic properties of concrete.